Teachers’ Skills in the Improvisation of Instructional Materials for Teaching Computer Studies in Junior Secondary School - Ikuereye, Evbakoe Pedro; Eganbor, Faith Enorense (Journal of Research in Industrial Technology and Educational Studies, 2025)
Improvisation can be an essential skill for teachers, especially in resource-constrained educational environments. The study investigated the skills of teachers in Egor Local Government Area of Edo State to improvise instructional materials for teaching when conventional resources are unavailable. Using a descriptive survey research design, the study sampled 102 teachers from 12 public Junior secondary schools. Data were collected through a structured questionnaire divided into sections addressing demographic information and the variable of interest. The instrument, validated by experts, achieved a reliability coefficient of 0.780 through Cronbach’s Alpha. Mean and standard Deviation was used to answer research question 1, t-test was used to test hypothesis 1 and ANOVA was used to test Hypothesis 2. at a 0.05 significance level. The findings revealed that teachers in the study area possess adequate improvisation skills, enabling them to adapt their teaching methods effectively in diverse situations. Teachers demonstrated the ability to create alternative instructional materials and found no variation in these skills based on gender, as male and female teachers exhibited similar proficiency levels in improvising teaching resources among others. Moreover, the study concluded that educational qualifications do not affect teachers’ improvisation abilities. Teachers across various qualification levels were equally adept at creating instructional materials. This uniformity suggests that the ability to improvise is a skill that transcends formal qualifications.